Analysis of submerged breakwater models using ripple tank - Mutmainnah; Viviq Ardita Wulandari; Roman Argus; Atmadi; Raditya Faradina Pratiwi; Imastuti (FoundAE, 2023)
A breakwater is an infrastructure that functions to dampen wave energy. To secure the area directly adjacent to the coast, an effective breakwater model is needed based on the analysis of the dissipation coefficient value ( ). This study aims to determine a good breaker model based on the Â value using a ripple tank. The data analyzed were wave heights before and after passing through the breakwaters of the three concrete models whose arrangement was varied. The results showed that the breaker model that is effective in reducing wave energy is the Grooved cube model with holes arranged horizontally based on the resulting small reflection coefficient ( ) and transmission coefficient ( ) values and large Â values